Genetic Evidence for Transboundary Circulation of Peste Des Petits Ruminants Across West Africa - Tounkara, Kadidia; Kwiatek, Olivier; Niang, Mamadou; Abou Kounta Sidibe, Cheik; Sery, Amadou; Dakouo, Martin; Salami, Habib; Lo, Modou Moustapha; Ba, Aminata; Diop, Mariame; El Mamy, Ahmed Bezeid; El Arbi, Ahmed Salem; et al. (Frontiers in Veterinary Science, 2019)
Peste des Petits Ruminants (PPR) is a viral disease affecting predominantly small ruminants. Due to its transboundary nature, regional coordination of control strategies will be key to the success of the on-going PPR eradication campaign. Here, we aimed at exploring the extent of transboundary movement of PPR in West Africa using phylogenetic analyses based on partial viral gene sequences. We collected samples and obtained partial nucleoprotein gene sequence from PPR-infected small ruminants across countries within West and Central Africa. This new sequence data was combined with publically available data from the region to perform phylogenetic analyses. A total of fifty-five sequences were obtained in a region still poorly sampled. Phylogenetic analyses showed that the majority of virus sequences obtained in this study were placed within genetic clusters regrouping samples from multiple West African and Central African countries. Some of these clusters contained samples from countries sharing borders. In other cases, clusters grouped samples from very distant countries. Our results suggest extensive and recurrent transboundary movements of PPR within West Africa, supporting the need for a regional coordinated strategy for PPR surveillance and control in the region. Simple phylogenetic analyses based on readily available data can provide information on PPR transboundary dynamics and, therefore, could contribute to improve control strategies. On-going and future projects dedicated to PPR should include extensive genetic characterisation and phylogenetic analyses of circulating viral strains in their effort to support the campaign for global eradication of the disease.